Analisis Pengunaan Lahan di Kabupaten Deli Serdang Kecamataan Pancur Batu Mengunakan Citra Google Earth - Sahala Fransiskus Marbun; Sania Agustina Br Subakti; Selfi Juwita Zamasi; Elno Situmorang; Lastri Marbun (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Pancur Batu District, as one of the areas in Deli Serdang Regency, is experiencing the dynamics of regional development and pressure on land. The total area of ​​Pancur Batu District in Deli Serdang Regency is 122.53 km2. Information on the current land use conditions is essential to support spatial planning and sustainable development policy making. This study aims to identify, map, and analyze the distribution of Sustainable development. This study aims to identify, map and analyze the distribution of land use in Pancur Batu sub-district by utilizing remote sensing technology. The method used is visual interpretation and on-screen digitization using high-resolution satellite imagery from Google Earth in 2024. Land use classification is divided into several main classes, such as settlements, open land and road networks. The main result of this study is a land use map of Pancur Batu sub-district with a 1: 63,360 map that presents a special distribution of each land use class. From the results of the map analysis, it is known that land use is dominated by open land. Meanwhile, identified residential areas are growing rapidly along the main road network. The resulting map can be accurate and up-to-date basic data for the Deli Serdang district government for monitoring, evaluating land suitability, and controlling space use in Pancur Batu sub-district.